Analysis of The Influence of Digital Literacy, Pedagogical Skills and Continuous Training on Teacher Competence: Penelitian - Dina Agnesia Sihombing; Rivi Antoni; Satria Riki Mustafa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research is meant to understand how digital literacy, educational skills, and constant training can made teacher competence grow in big cities of Indonesia. The study was carried out using a qualitative approach and a descriptive method. Data were gathered through interviews which were structured and in-depth with 30 teachers from different levels of education. Principals of the schools were involved as supporting informants to get a wider perspective. The results reveal that digital literacy is extremely important to a teacher as it helps him or her to incorporate technology into the teaching and learning process. Besides that, pedagogical skills equip the teacher with the ability of planning, implementation, and evaluation of the desired learning experiences that are in line with the pupils' needs. The continuous training is also very important as it allows the teachers to keep their knowledge up-to-date, their skills developed, and their professionalism maintained amid the constant changes in the field of education. This study suggests schools and policymakers to improve teacher training programs with more energy, support the use of technology in education, and create a work environment that is conducive to collaboration and continuous professional development.